2017
DOI: 10.1088/1361-6455/aa53ec
|View full text |Cite
|
Sign up to set email alerts
|

E1, M1, E2 transition energies and probabilities of W54+ions

Abstract: Abstract. A comprehensive theoretical study of the E1, M1, E2 transitions of Ca-like tungsten ion is presented. Using multi-configuration Dirac-Fock (MCDF) method with a restricted active space treatment, the wavelengths and probabilities of the M1 and E2 transitions between the multiplets of the ground state configuration (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…The discrepancies of the transition wavelengths and rates with the present calculation are about 0.07% and 0.01%, respectively. Ding et al [23] have included somewhat more electron correlations by extending the correlation configurations to include single and double excitation from the n = 3 complex to n ≤ 6 subshells, and the discrepancies of the transition wavelengths and rates with the present calculation are about 0.02% and 0.03%, respectively. Safronova et al [16] started their calculation based on the Dirac-Fock potential of the 1s 2 2s 2 2p 6 3s 2 3p 6 core configuration for Ca-like tungsten ion by RMBPT.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The discrepancies of the transition wavelengths and rates with the present calculation are about 0.07% and 0.01%, respectively. Ding et al [23] have included somewhat more electron correlations by extending the correlation configurations to include single and double excitation from the n = 3 complex to n ≤ 6 subshells, and the discrepancies of the transition wavelengths and rates with the present calculation are about 0.02% and 0.03%, respectively. Safronova et al [16] started their calculation based on the Dirac-Fock potential of the 1s 2 2s 2 2p 6 3s 2 3p 6 core configuration for Ca-like tungsten ion by RMBPT.…”
Section: Resultsmentioning
confidence: 58%
“…Many research works on the radiative properties of tungsten ions related to fusion in various ionization stages have been published in the past several decades [5][6][7][8][9][10][11][12][13]. Special attention has been paid to the magnetic dipole (M1) transitions of the W 54+ ion [14][15][16][17][18][19][20][21][22][23]. In their electron beam ion trap (EBIT) experiment, Ralchenko et al [14] observed two emission peaks at 14.986 nm and 17.144 nm, which they identified with M1 transitions between the levels of the ground configuration [Ne]3s 2 3p 6 3d 2 of W 54+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And some transitions with wavelength in 18. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].6Å are suggested to be observed in the future experiment.…”
Section: Introductionmentioning
confidence: 74%
“…Lennartsson et al observed the electric dipole (E1) transitions from the excited states [Ne]3s 2 3p 5 3d 3 to the ground state [Ne]3s 2 3p 6 3d 2 of W 54+ ion in the wavelength range of 26.3-43.5Å in the Lawrence Livermore National Laboratory (LLNL) EBIT at the electron beam energy of 18.2 keV, and a CRM was applied to explain the observed spectrum [13]. Ding and his collaborators have performed a calculation on the E1, E2, M1, M2 transitions between [Ne]3s 2 3p 5 3d 3 and [Ne]3s 2 3p 6 3d 2 levels of W 54+ ion by using an MCDF method with the restricted active space method; the relativistic and electron correlation effects as well as the Breit interaction and some Quantum Electrodynamic effects have been taken into account [11,19,20]. The results are in reasonable agreement with available experimental data for both M1 and E1 transition lines.…”
Section: Introductionmentioning
confidence: 99%